The Role of Brand Personality in Determining the Success of Green Marketing Strategies - Nuriya Fadilah; Muh. Syarif; Suyono Suyono (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the role of brand personality in the success of green marketing strategies, focusing on the dimensions of sincerity, excitement, competence, and sophistication. The findings indicate that these dimensions significantly enhance consumer trust, loyalty, and purchase intention toward environmentally friendly products. Green marketing influences consumer behavior through both functional and emotional aspects, with external factors such as consumer values, regulations, and market context acting as moderators. These findings provide practical implications for companies to strengthen brand personality and ensure transparency in sustainability claims, while also offering opportunities for further research on the external factors influencing green marketing strategies.